Linoleic Acid Status in Cell Membranes Inversely Relates to the Prevalence of Symptomatic Carotid Artery Disease. Issue 2 (February 2021) - Lázaro, Iolanda; Cofán, Montserrat; Amor, Antonio J.; Ortega, Emilio; Freitas-Simoes, Tania-Marisa; Llull, Laura; Amaro, Sergio; Mestres, Gaspar; Yugueros, Xavier; Harris, William S.; Riambau, Vicente; Sala-Vila, Aleix
Abstract : Background and Purpose: The red blood cell fatty acid composition objectively reflects the long-term dietary intake of several fatty acids. In patients undergoing carotid endarterectomy, we explored whether red blood cell status of selected fatty acids related to symptomatic carotid artery disease. Methods: We included patients with symptomatic (n=22) and asymptomatic (n=23) carotid artery disease. We determined all-C18:1 trans, linoleic acid (LA, C18:2n6), alpha-linolenic acid (C18:3n3), and the omega-3 index (sum of eicosapentaenoic [C20:5n3] and docosahexaenoic [C22:6n3] acids) in both red blood cells and carotid plaque phospholipids by gas-chromatography. Results: In a multivariate logistic regression analysis, we only observed a significant association for LA, whose red blood cell status was inversely related to symptomatic carotid artery disease (odds ratio, 0.116 [95% CI, 0.022–0.607], P =0.011, for each 1-SD increase). A similar result was observed for LA in carotid plaque phospholipids. Conclusions: Cell membrane enrichment in LA, which reflects its intake, was inversely related to symptomatic carotid disease. This increases evidence supporting a favorable role of dietary LA in vascular health. Abstract : Supplemental Digital Content is available in the text.